(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Fitness to practice (FTP) is a concept fundamental to nursing, such that practitioners are held to professional, ethical, and clinical standards for delivering safe patient care. Fitness to practice has no clear operational definition among the regulatory agencies, curriculum in academe, and health care settings. Objective: This research is proposed to examine and define the concept of fitness to practice in the practice of nursing through Walker and Avant’s concept analysis framework. Methods: This paper uses Walker and Avant’s eight-step approach to analyze the uses, defining characteristics, antecedents, consequences, and empirical referents of the FTP concept. Literature was obtained from CINAHL, PubMed, and Scopus databases (2010–2025) with emphasis on regulation, clinical competence, impairment, and ethics. Results: The most important characteristics of fitness to practice are clinical competence, psychological and physical health, ethical conduct, and compliance with professional standards. Antecedents are educational preparation, licensure, and regulatory mechanisms. Consequences of compromised FTP are patient injury, professional misconduct, and licensure revocation. A model case is illustrated with borderline and contrary cases to illustrate concept clarity. Conclusion: Clearing fitness to practice improves regulatory uniformity and guides policy, education, and intervention activities related to the delivery of safe, competent nursing practice.